Adoption of Agricultural E-Marketing: Application of the Theory of Planned Behavior. Issue 1 (2nd January 2017) - Alavion, Seyed Jaber; Allahyari, Mohammad Sadegh; Al-Rimawi, Ahmad Shukri; Surujlal, Jhalukpreya
ABSTRACT: In this study, the authors used the theory of planned behavior (TPB) as a base model to determine how attitudes, subjective norms, and perceived behavioral control predict the intention of agricultural services professionals to adopt e-marketing of agricultural commodities. A convenient sample of 146 professionals from the public ( n  = 61) and private sectors ( n  = 85) were surveyed. Overall, results showed that the TPB model explained 94% and 71% of the variation in behavioral intent for public professionals and private professionals, respectively, with the remaining 6% and 29% relating to the other factors. Results for the public professionals showed that subjective norm and perceived behavioral control have a more important effect on adoption and that the effect of attitude was very small among professionals in private sector. Both groups selected the information services model as an appropriate in agricultural electronic marketing for local farmers so that agricultural services firms can offer only information services of farmers' products without a direct role in buying and selling. Based on the results, it is recommended that to accelerate the adoption of e-marketing, its user-friendliness and advantages should be demonstrated to users via different platforms such as video presentations and workshops. In addition, the technology should be made available to potential users, and they should be encouraged and motivated to use it to ensure efficiency in the processing of transactions.